Pemberdayaan Ibu Pasca Bersalin, Keluarga, tentang PHBS, Perawatan Ibu dan Bayi serta Pencegahan Penularan COVID-19 - Islah Wahyuni; Ulfa Hasanah; Novi Yanti; Ifon Driposwana Putra (LPPM Akbid Harapan Ibu Pekalongan, 2020)
Covid-19 pandemic is determined as non-natural disaster, because its rapid transmission and endanger humans, especially pregnant women, childbirth, post-partum, newborns. The increase ofincidence number that befall the community from day to day, there are still families and postpartum mothers who do not understand in postnatal maternal and infant health care and prevention of covid transmission 19. to increase family participation and knowledge of postpartum mothers about maternal and infant health care in the prevention of Covid-19 transmission and its application during the first week of her baby's birth at home. This coaching was implementating from April to June 2020 on 20 post partum mothers while being treated at the midwife clinic and during homecare services in the first week, by providing education, fill post-test questionnaire, observing the implementation of maternal and infants careand Covid 19 prevention at home. Family participation increased by 16 people (80%), Post-Test Knowledge was good for 17 people (85%), Good Mother and Baby Care Techniques for 13 people (65%). It is hoped that postpartum motherswill continue to carry out maternal and infant care and prevention of Covid 19 during the pandemic period as suggested by the midwife.